2009
DOI: 10.1038/jhg.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

The key role of patrilineal inheritance in shaping the genetic variation of Dagestan highlanders

Abstract: The Caucasus region is a complex cultural and ethnic mosaic, comprising populations that speak Caucasian, Indo-European and Altaic languages. Isolated mountain villages (auls) in Dagestan still preserve high level of genetic and cultural diversity and have patriarchal societies with a long history of isolation. The aim of this study was to understand the genetic history of five Dagestan highland auls with distinct ethnic affiliation (Avars, Chechens-Akkins, Kubachians, Laks, Tabasarans) using markers on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
2
19
0
1
Order By: Relevance
“…Some studies have shown that neither geography nor linguistics have had a strong influence on the genetic structure 23 . Geography, rather than language, was claimed to provide a better explanation for the observed genetic structure by the majority of studies 15,20,22,24 , while parallel evolution of Y chromosome and language variation was supported by Balanovsky et al 16 . We suggest that part of the explanation for these diverse conclusions came from differences in sampling schemes.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Some studies have shown that neither geography nor linguistics have had a strong influence on the genetic structure 23 . Geography, rather than language, was claimed to provide a better explanation for the observed genetic structure by the majority of studies 15,20,22,24 , while parallel evolution of Y chromosome and language variation was supported by Balanovsky et al 16 . We suggest that part of the explanation for these diverse conclusions came from differences in sampling schemes.…”
mentioning
confidence: 83%
“…Its compact distribution of deeply divergent languages 4 provides a unique possibility to test gene-language co-evolution at a fine scale and to illuminate the genomic footprint of events such as migration and admixture on genetic variation. However, most previous genetic studies either did not perform dense sampling of the region, or were limited to autosomal Alu insertion, autosomal STR, Y-chromosomal, and mtDNA surveys [14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] Limited pedigree data suggest very high mean inbreeding coefficients (0.005-0.0134), 32,37 whereas population genetic studies have been restricted to autosomal Alu insertion and STR markers, the Y chromosome and mtDNA. 32,[37][38][39][40][41][42][43][44][45] …”
Section: Introductionmentioning
confidence: 99%
“…Elbrus) and show archeological and genetic evidence of continuous human occupation since >10,000 Ybp (Caciagli et al 2009), so provide an additional environment where humans have adapted to high altitude. The geo-morphological, anthropological, and linguistic landscapes are all very complex.…”
Section: Introductionmentioning
confidence: 99%
“…The geo-morphological, anthropological, and linguistic landscapes are all very complex. For example, several distinct ethnic groups live at high altitudes in the Republic of Daghestan (Russia) speaking Caucasian, Indo-European or Altaic languages (Caciagli et al 2009). Anthropological and genetic studies have shown that the majority of these groups have high endogamy, high inbreeding, and small population sizes that have remained stationary for many generations (Bulayeva et al 2005, 2006).…”
Section: Introductionmentioning
confidence: 99%